Analysis and Improvement of Low Internal Pressure of Air Spring Load on Guangzhou Metro Line 3 Train - Xiaofeng JING; Shaoji CHEN; Liang ZHANG (机车电传动)
In order to solve the problem that the internal pressure of air spring load on Guangzhou metro line 3 train was low to affect the performance of the train, the causes were analyzed, and the specific scheme of improving the air spring system was determined by comparing the laboratory test and loading data measurement. The improved product has been verified by type test and loading verification, which has reliable performance and effectively solved the problem of low internal pressure of air spring load, and eliminates potential safety hazards.